2011
DOI: 10.1542/peds.2010-2743
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Sudden Death in Young, Competitive Athletes Due to Blunt Trauma

Abstract: WHAT'S KNOWN ON THIS SUBJECT:Fatalities caused by blunt trauma are known to occur in children and adolescents in a variety of circumstances, including while engaged in competitive in sports. WHAT THIS STUDY ADDS:This unique national database provides a prevalence for trauma-related catastrophes in children, adolescents, and young adults aged 21 or younger; establishes the epidemiology of events for which football conveys highest risk; and provides visibility to underrecognized mortality risks associated with "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(52 citation statements)
references
References 33 publications
(56 reference statements)
1
50
0
1
Order By: Relevance
“…Consequently, athletes are more likely to experience a subsequent concussion while still symptomatic from the initial injury [20][21][22][23]. Although rare, there may be an elevated risk of mortality among athletes who sustain additional brain trauma during the neurologically vulnerable period following their initial injury [24].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, athletes are more likely to experience a subsequent concussion while still symptomatic from the initial injury [20][21][22][23]. Although rare, there may be an elevated risk of mortality among athletes who sustain additional brain trauma during the neurologically vulnerable period following their initial injury [24].…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective review of sudden death caused by subdural hematoma in athletes 14-18 years of age demonstrated a 12% incidence of prior concussion with persistent symptoms. 65 Secondimpact syndrome, a consequence of repeat head injury, is thought to result from rapid and malignant cerebral edema. Note, however, that the syndrome has been described predominantly through case reports and is still poorly understood.…”
mentioning
confidence: 99%
“…1 Moreover, it is abundantly clear that the catastrophic second-impact syndrome is both real and preventable. 4,5 It is imperative, then, that the concussed athlete be identified (especially when signs and symptoms are subtle), and then allowed to return to play only after resolution of symptoms. These tasks can best be accomplished by combining clinical judgment with a standardized, validated tool.…”
Section: Discussionmentioning
confidence: 99%